Process evaluation of a multi-disciplinary complex intervention to improve care for older patients with chronic conditions in rural areas (the HandinHand Study): study protocol - Swantje Seismann-Petersen; Sascha Köpke; Simone Inkrot (BMC, 2022)
Abstract Background To improve health care in rural areas, especially for increasing numbers of people with chronic diseases, academically qualified nurses could take over expanded roles to meet the challenges of an ageing society and a decreasing number of General Practitioners (GPs). In the project "HandinHand" (HiH), qualified nurses (Expert nurses, ENs) will carry out home visits to older people with chronic diseases over a period of six months. ENs will prepare a care plan in cooperation with GPs to stabilise the care situation and avoid unplanned hospital admissions and GP visits. The process evaluation aims to provide an in-depth analysis of the implementation process and gather important information on barriers and facilitators to the implementation of ENs as a complementary health care structure in primary care, taking into account several context factors. Methods Based on the Medical Research Council (MRC) Framework for complex interventions, a logic model was developed and applied as the basis for data collection. Qualitative and quantitative data will be collected during the study. A mixed methods approach should allow to gain important insights from participants (e.g. ENs, GPs, patients) involved in the study as well as relevant stakeholders. Semi-structured interviews and surveys will be conducted. Data analysis will be based on the logical model, combining qualitative and quantitative data. Qualitative data will be analysed inductively-deductively using qualitative thematic framework analysis. Discussion The process evaluation will provide guidance and conclusions on further development and transferability. Of particular interest is the expanded role of ENs in primary care, which has barely been implemented in Germany and can be seen as a precursor to the development of an Advanced Practice Nursing (APN) role in primary care.